2016
DOI: 10.3847/0004-6256/152/2/42
|View full text |Cite
|
Sign up to set email alerts
|

Alma Observations of HCN and Its Isotopologues on Titan

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. , and HCN/H 13 C 15 N=5800±270 (1σ errors). The carbon and nitrogen ratios are consistent with and improve on the precision of previous results, confirming a factor of ∼2.3 elevation in 14 N/ 15 N in HCN compared to N 2 and a lack of fractionation in 12 C/ 13 C from the protosolar value. This is the first published measurement of D/H in a nitrile species on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 44 publications
4
63
0
Order By: Relevance
“…More specifically, the modeled 14 N/ 15 N values for CH 3 CN and C 2 H 5 CN are ∼80 at high altitudes (∼800 km) and increase to ∼120 in the lower stratosphere (∼200 km), while those for HCN and HC 3 N are expected to be relatively constant at ∼80 altitudes below 800 km. These modeled values for HCN and HC 3 N are in good agreement with previous observation results of 94±13 (Gurwell 2004) and 72.2±2.2 (Molter et al 2016) for HCN, and 67±14 (Cordiner et al 2018) for HC 3 N. Interestingly, there is another photochemical model showing different 14 N/ 15 N values for nitriles. Vuitton et al (2019) modeled nitrile chemistry including isotopic fractionation processes, which indicated that 14 N/ 15 N for CH 3 CN at high (>1000 km) altitude is smaller than that of HCN and HC 3 N because they proposed that CH 3 CN is produced from N( 2 D) which is enriched in 15 N. In turn, in the lower stratosphere (at 200 km), three nitriles are expected to exhibit similar 14 N/ 15 N values of ∼55 because non-fractionated N-atoms produced by GCR collision with N 2 homogenizes 14 N/ 15 N in nitriles via recycling processes.…”
Section: Introductionsupporting
confidence: 92%
“…More specifically, the modeled 14 N/ 15 N values for CH 3 CN and C 2 H 5 CN are ∼80 at high altitudes (∼800 km) and increase to ∼120 in the lower stratosphere (∼200 km), while those for HCN and HC 3 N are expected to be relatively constant at ∼80 altitudes below 800 km. These modeled values for HCN and HC 3 N are in good agreement with previous observation results of 94±13 (Gurwell 2004) and 72.2±2.2 (Molter et al 2016) for HCN, and 67±14 (Cordiner et al 2018) for HC 3 N. Interestingly, there is another photochemical model showing different 14 N/ 15 N values for nitriles. Vuitton et al (2019) modeled nitrile chemistry including isotopic fractionation processes, which indicated that 14 N/ 15 N for CH 3 CN at high (>1000 km) altitude is smaller than that of HCN and HC 3 N because they proposed that CH 3 CN is produced from N( 2 D) which is enriched in 15 N. In turn, in the lower stratosphere (at 200 km), three nitriles are expected to exhibit similar 14 N/ 15 N values of ∼55 because non-fractionated N-atoms produced by GCR collision with N 2 homogenizes 14 N/ 15 N in nitriles via recycling processes.…”
Section: Introductionsupporting
confidence: 92%
“…36489corr been used extensively as a dense gas tracer in external galaxies (e.g., Schirm et al 2016;Sliwa & Downes 2017;Johnson et al 2018). HCN is also very abundant in the atmosphere of Titan, and has been used to measure nitrogen fractionation there (e.g., Molter et al 2016). CH 3 CN is regularly used to determine kinetic temperature in star-forming regions (Bell et al 2014), and HC 3 N has been shown to be important in observations of ultraluminous infrared galaxies (Costagliola et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Dashed green lines plotted for the DM Tau (Teague et al 2015) and TW Hya ) disks represent the range of values derived for various radii. Purple squares represent values for the following individual sources: TMC-1 (Wootten 1987), low-mass protostar IRAS 16293-2422 (Schöier et al 2002), the TW Hya disk (Öberg et al 2012), comet HaleBopp (Meier et al 1998), and Titan (Molter et al 2016).…”
Section: Comparison To Disk Modelsmentioning
confidence: 99%